Electronic Commerce in Increase the Competitiveness of the Country's Economy - Makhmudovich, Baymuradov Shokhrukh (Research Parks Publishers, 2023)
What areas should be developed and what reforms should be implemented to increase the competitiveness of the country's economy. At a time when all countries are on the path of development, issues such as how Uzbekistan can increase its competitiveness and the role of electronic trade in this have been considered.